Exploring E-Repurchase Intention of Online SMEs in Tangerang: How The Role E-Satisfaction and E-service Quality? - Adi Widodo; Multi Nadeak; Dewiana Novitasari; Tias Pramono; Gusli Chidir (Universitas Negeri Makassar, 2022)
The purpose of this study was to analyze the effect of E-satisfaction on E-repurchase intention of Online SMEs users, to determine the positive effect of E-service quality on E-repurchase intention of online SMEs and to determine the positive effect of E-service quality on e-satisfaction. of Online SMEs. This research is focused on SMEs Online consumers in Tangerang, this type of research is quantitative with a sample of 566 respondents with the data collection method using a questionnaire via google form, using a non-probability sample. Data analysis using SmartPLS version 3.0 software. And based on the results of the analysis it was concluded that E-satisfaction had a positive and significant effect on E-repurchase intention, E-service quality had a positive and significant effect on E-repurchase intention of online SMEs and E-service quality had a positive and significant effect on e-satisfaction of Online SMEs.